A single fluorescent chemosensor for multiple targets of Cu2+, Fe2+/3+ and Al3+ in living cells and a near-perfect aqueous solution. Issue 46 (31st May 2017) - Jo, Tae Geun; Jung, Jae Min; Han, Jiyeon; Lim, Mi Hee; Kim, Cheal
Abstract : A naphthol-based chemosensor1 was developed for detection of Cu 2+ and Fe 2+/3+ by fluorescence quenching and Al 3+ by fluorescence emission change. Abstract : A sulfonate-based chemosensor1 was designed and synthesized for sensing various analytes: Cu 2+, Fe 2+/3+ and Al 3+ . Sensor1 showed a high selectivity and sensitivity for the analytes in a near-perfect aqueous medium. Cu 2+ and Fe 2+/3+ could be monitored by fluorescence quenching of1 . It had sufficiently low detection limits (1.25 μM for Cu 2+ and 3.96 μM for Fe 3+ ), which were below the recommended levels of the World Health Organization for Cu 2+ (31.5 μM) and the Environmental Protection Agency for Fe 3+ (5.37 μM).1 showed the high preferential selectivity for Cu 2+ and Fe 3+ in the presence of competitive metal ions without any interference. Importantly, pyrophosphate could be used to distinguish Fe 3+ from Cu 2+ . In addition, this sensor could monitor Al 3+ through fluorescence emission change. Moreover, 1 was successfully applied to quantify and image Al 3+ in water samples and living cells. Based on photophysical studies and theoretical calculations, the sensing mechanisms of1 for Cu 2+ and Al 3+ were explained, respectively.